Temporal Dynamics of Soil Nitrogen Pools and Nutrient Flux in Maize as Affected by Leguminous Biomass Decomposition - Kumar, S. Vijay; Bindu, G. S. Madhu; Padmaja, B.; Reddy, G. Kiran; Latha, P. C.; Jahnavi, B.; Ramakrishna, K.; Babu, Charan A.; Kundu, Santanu; Poojasree, E. (International Journal of Bio-resource and Stress Management, 2026)
A field experiment was conducted during the rabi (winter) season (November, 2022 to March, 2023) at the College Farm, Professor Jayashankar Telangana Agricultural University (PJTAU), Hyderabad, Telangana, India to study the effect of in situ green manuring on soil nitrogen dynamics in intensive maize systems. The experiment was laid out in a randomized block design with eight treatments. Maize (var. DHM 117) was sown in paired rows, while sunhemp was simultaneously established in between and incorporated in situ at 45 days after sowing (DAS). Nitrogen was applied at the tasselling stage in graded levels from 0 to 60 kg N ha-1 in green manured plots (T1 -T7) and compared with a farmer’s practice of recommended fertilizer dose (RDF) of 240 kg N ha-1 without green manuring (T8). Soil samples collected at major crop stages were analysed for ammonical nitrogen, nitrate nitrogen, total nitrogen, total carbon, and carbon-to-nitrogen (C:N) ratio. Green manuring significantly enhanced soil nitrogen fractions compared to sole maize. At tasselling, ammonical nitrogen (54.3-55.5 mg kg-1) and nitrate nitrogen (44.4 - 45.4 mg kg-1) were higher under green manuring than in the control (52.5 and 41.8 mg kg-1, respectively). Total soil nitrogen also improved (0.0382 - 0.0420%) compared to 0.0360% in the control. Among treatments, GM+30 kg N ha-1 and GM + 60 kg N ha-1 consistently exhibited superior nitrogen status and C: N balance, indicating that in situ sunhemp incorporation with optimal N supplementation sustains soil quality and nutrient availability in rabi maize systems.